PENGARUH RASIO CAMEL TERHADAP PRAKTIK MANAJEMEN LABA PADA BANK DI INDONESIA - Anifah Nurshofyani (MM UMY, 2016)
This study aimed to examine the effect of the ratio CAMELS on earnings management practices at banks in Indonesia. This study uses secondary data from the bank's annual financial statements published during 2007 and 2013. The sampling technique used is purposive sampling consisting of 175 annual financial statements of the 25 sample banks. Earnings management in this study is proxied by discretionary accruals that have been adapted to the characteristics of banking in Indonesia. The determination of the coefficient of earnings management is done with total accruals calculated regression model with Healy and Jones. Testing indicated the presence of earnings management practices conducted by One Sample T-Test and testing the effect of CAMEL ratio to earnings management performed by Multiple Linear Regression Test. Based on the classic assumption test: normality test, multicollinearity, heteroscedasticity test and autocorrelation test indicates that the available data has been qualified. The results showed, on average, there is an indication of earnings management practices at banks in Indonesia. The results by multiple regression test shows for variable CAR and NPL significant negative effect on earnings management practices, while variable OER, ROE, and LDR significant negative effect on earnings management practices at banks in Indonesia.